2020
DOI: 10.3390/ijms21197176
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Fibulin-2 in Hypertrophic Cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common inherited heart muscle disease, with a prevalence of at least 1 in 500 in the general population. The disease is pleiotropic and is characterized by an increased stiffness of the myocardium, partly due to changes in the extracellular matrix (ECM), with elevated levels of interstitial fibrosis. Myocardial fibrosis is linked to impaired diastolic function and possibly phenotypic heterogeneity of HCM. The ECM consists of a very large number of proteins, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [ [133], Jiang et al [134], Yu et al [135], Jiang et al [136], Huang et al [137], Scuruchi et al [138], Wang et al [139], Ibrahim et al [140], Zha et al …”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [ [133], Jiang et al [134], Yu et al [135], Jiang et al [136], Huang et al [137], Scuruchi et al [138], Wang et al [139], Ibrahim et al [140], Zha et al …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have well demonstrated that excessive accumulation of ECM impaired cardiac contractile function and emphasized the role of myocardial brosis in the morphogenesis and establishment of HCM (32,33). Abnormal expression of ECM components like Fibulin-2 and TXNDC5 might augment detrimental interactions in HCM (34,35) and HCM-related matrix undermined healthy cardiomyocytes with prolonged contractions and poor relaxation (36). Additionally, TGF-beta signaling pathway, which is relatively negative enriched in TUBA3D, participates in pathogenesis and development of HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic aortic biopsies were collected, processed and prepared for staining as described before 25 . Briefly, for fibrous collagen staining, slides were incubated in picrosirius red stain (Abcam) for 1 hr and washed in 0.5% acetic acid for differentiation.…”
Section: Tissue Processing and Histological Stainingmentioning
confidence: 99%
“…Section preparation was performed as described before 25,26 . All antibodies were diluted using blocking solution; α-SMA 1:300 (Thermo Scientific™, # MS- Rabbit IgG H&L Alexa Fluor® 488) (Abcam, #ab150077) at a 1:500 dilution, incubated in the dark for 1 hr at RT, and then mounted with DAPI-containing mounting media (Invitrogen™, Carlsbad, CA, USA, #P36962).…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation